The prediction of two-dimensional PbN: opened bandgap in heterostructure with CdO - Cheng, Zhang; Wang, Yuelei; Zheng, Ruxin; Mu, Weihua (Frontiers in Chemistry, 2024)
Two-dimensional (2D) materials have been developed by wide attention in as generation of optoelectronics, thermoelectric and other applications. In this work, a novel 2D material, PbN, has been proposed by elemental method using the prototype of the recent reported nitride (J. Phys. Chem. C 2023, 127, 43, 21006–21014). Based on first-principle calculations, the PbN monolayer is investigated as stable at 900 K, and the isotropic mechanical behavior is addressed by the Young’s modulus and Poisson’s ratio as 67.4 N·m–1 and 0.15, respectively. The PbN monolayer also presents excellent catalytic performance with the Gibbs free energy of 0.41 eV. Besides, zero bandgap is found for the PbN monolayer, while it can be opened as about 0.128 eV by forming a heterostructure with CdO. Furthermore, the PbN/CdO is constructed by van der Waals interaction, while the apparent potential drop and charge transfer are investigated at the interface. The PbN/CdO heterostructure also possesses an excellent light absorption properties. The results provide theoretical guidance for the design of layered functional materials.